1995
DOI: 10.1128/aem.61.12.4348-4356.1995
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and analysis of the prolate-headed lactococcal bacteriophage c2 genome and identification of the structural genes

Abstract: The 22,163-bp genome of the lactococcal prolate-headed phage c2 was sequenced. Thirty-nine open reading frames (ORFs), early and late promoters, and a putative transcription terminator were identified. Twenty-two ORFs were in the early gene region, and 17 were in the late gene region. Putative genes for a DNA polymerase, a recombination protein, a sigma factor protein, a transcription regulatory protein, holin proteins, and a terminase were identified. Transcription of the early and late genes proceeded diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(68 citation statements)
references
References 48 publications
5
62
0
1
Order By: Relevance
“…The two phages infecting S. aureus FH5 and vB_SauS-phiIPLA35 (F35) belonged to morphotype B1 and morphotype B2, respectively, and their complete genome sequence was available (García et al, 2007(García et al, , 2009). Finally, the lytic L. lactis phage FC2 belonging to the morphotype B2 (Lubbers et al, 1995) was chosen as representative of phages infecting a different genus within Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The two phages infecting S. aureus FH5 and vB_SauS-phiIPLA35 (F35) belonged to morphotype B1 and morphotype B2, respectively, and their complete genome sequence was available (García et al, 2007(García et al, , 2009). Finally, the lytic L. lactis phage FC2 belonging to the morphotype B2 (Lubbers et al, 1995) was chosen as representative of phages infecting a different genus within Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence of sk1 ORF50 is 93% identical to the homologous ORF from bIL66, but there are no homologues of sk1 ORF48 and ORF49 in bIL66. Comparison of the genomes of the prolate-headed L. lactis phage c2 and bIL67 has shown that deletion/insertion of discrete ORFs is associated with the presence of direct repeats flanking the deleted DNA (Lubbers et al, 1995). No direct repeats were observed in the sk1 regions flanking ORF48 and ORF49, suggesting that a similar mechanism of deletion/insertion had not occurred in sk1.…”
Section: Sequencing Of Sk1 Dna and Identification Of Orfsmentioning
confidence: 99%
“…sk1 ORF53 shares homology with an ORF in the prolate-headed phages c2 and bIL67 (Table 1). Lubbers et al (1995) suggested that this ORF could be the phage holin, but the sk1 holin is encoded by ORF19 in the late region of the phage (see below).…”
Section: The Middle Regionmentioning
confidence: 99%
See 2 more Smart Citations